FORMULASI SEDIAAN GARGARISMA DARI EKSTRAK BUAH BELIMBING WULUH (Averrhoa bilimbi L) SEBAGAI ANTI KANDIDIASIS - Ega Pratama; Adilla Edi Arief (STIKes Muhammadiyah Kuningan, 2018)
Gargarisma a cleaning solution used as a mouth or treatment of diseases of the oral mucous membrane. Has done research of gargarisma formulation with active substanc extract berambibul wuluh fruit (averrhoa bilimbi L) as anti kandidiasis. The extraction used to obtain the extract of star fruit starfruit is a maceration exstract with 96% ethanol solvent with 4 times the replacement of solvent, then steamed with water bath, extracts obtained 90 grams and made 3 gargarisma formulations extract of starfruit berries with different concentrations of 6%, 8%, 10%. Based on the organoleptic have a distinctive liquid and odor shape, then based on homogenous test of homogeneous preparations, from pH test results of formula 1, 2 and 3 with pH 3 while the 3rd formulation of pH change occurred on days 21 and 28 with pH 2. Stability test results for 28 days at room temoerature (25o – 300c) showed that formula 1 remained stable while formulas 2 and 3 changed color.